Risk factors for carbapenem-resistant Pseudomonas aeruginosa infection in a tertiary care hospital in Serbia - Djordjevic, Zorana; Folic, Marko; Ruzic Zecevic, Dejana; Ilic, Goran; Jankovic, Slobodan (The Journal of Infection in Developing Countries, 2013)
This item has no abstract. Follow the links below to access the full text